2019
DOI: 10.3390/ma12030452
|View full text |Cite
|
Sign up to set email alerts
|

Study of Two Bovine Bone Blocks (Sintered and Non-Sintered) Used for Bone Grafts: Physico-Chemical Characterization and In Vitro Bioactivity and Cellular Analysis

Abstract: In this work, the physicochemical properties and in vitro bioactivity and cellular viability of two commercially available bovine bone blocks (allografts materials) with different fabrication processes (sintered and not) used for bone reconstruction were evaluated in order to study the effect of the microstructure in the in vitro behavior. Scanning electron microscopy, X-ray diffraction, Fourier transform infrared spectrometry, mechanical resistance of blocks, mercury porosimetry analysis, in vitro bioactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…The physical characteristics of both materials were evaluated using scanning electron microscopy (SEM, Hitachi S-3500N, Tokyo, Japan). Regarding the physico-chemical structural features, crystallinity, chemical composition, mechanical resistance, porosity, trabecular density, gas and fluid intrusion, cell adhesion, viability, and proliferation of the two employed materials were similar, as a previous study published by our group has shown [25]. The biodegradability test suggested a higher dissolution rate of the nonsintered versus the sintered bovine blocks by day 14.…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…The physical characteristics of both materials were evaluated using scanning electron microscopy (SEM, Hitachi S-3500N, Tokyo, Japan). Regarding the physico-chemical structural features, crystallinity, chemical composition, mechanical resistance, porosity, trabecular density, gas and fluid intrusion, cell adhesion, viability, and proliferation of the two employed materials were similar, as a previous study published by our group has shown [25]. The biodegradability test suggested a higher dissolution rate of the nonsintered versus the sintered bovine blocks by day 14.…”
Section: Methodssupporting
confidence: 78%
“…The temperatures applied during the sintering process can alter a material's physical properties, such as pore morphology and size, density, particle size, compressive strength, and torsional force [12]. Moreover, with the change in specific surface area, density, and porosity, a material's metabolic features (e.g., dissolution and/or resorption) can also be affected [20,25].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings correspond to viewpoints that calcium phosphate ceramics not only play a role in bone formation but also offer temporary support through the mechanism of creeping-substitution [4,5]. Physicochemical characteristics of DCP/HA bioceramics are crucial for efficacy in bone regeneration [48][49][50].…”
Section: Discussionsupporting
confidence: 88%
“…In contrast to autogenous grafts, BSMs do not contain organic components such as osteogenic cells or growth factors such as BMP-2 (bone morphogenic protein-2) and a VEGF (vascular endothelial growth factor) and they also may not contain collagen structures and fibers, enabling an osteoconductive and inductive regenerative potential in autogenous grafts. Thus, different BSM preparation methods and processes could affect the regeneration and surface characteristics of xenogeneic BSMs [19][20][21][22]. Accordingly, BSM sintering under a temperature >1000 • C seems to remove all organic compounds, thereby excluding an immune reaction and disease transmission and increasing crystallinity and volume stability [13,21,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%